Effect of thermosonication in a laboratory-scale continuous system on the survival of thermophilic bacteria and indigenous microbiota in milk - Deshpande, V. K. (2023)
Fluid foods are typically heat-treated to eliminate pathogens and reduce microbial counts. Coupling thermosonication with heat may reduce the microbial load in fluid foods and enhance the product quality during storage. This study evaluated the effect of thermosonication along with heat in a laboratory-scale continuous system, on the survival of Geobacillus stearothermophilus in milk, at two different settings (setting 1: 27.7 s total heating time with or without 11.9 s of sonication; setting 2: 20.3 s total heating time with or without 7.1 s of sonication). This study also investigated the effect of thermosonication along with heat on indigenous microbiota in raw milk; and milk quality was assessed by pH, free fatty acid (FFA) content, and casein/total protein (CN/TP) content during storage at the two different settings. Overall, thermosonication with heat resulted in higher log reductions for G. stearothermophilus; but, the reduction was not significant overall. Thermosonication with heat significantly decreased the indigenous microbiota in milk as compared to heat alone at both settings. Longer residence times (setting 1) had significantly higher log reductions at week 0, and treatment samples had significantly higher reductions than control during storage time at both the settings. Treatment samples at setting 1 had significantly higher pH and CN/TP, and lower FFA content at week 4, as compared to the control. Thermosonication using practical residence times along with heat may reduce milk microbiota. Results from this study need to be verified in a scale-up study employing pasteurization conditions.